Representasi Seksualitas dalam Novel Saman Karya Ayu Utami - Chairiyani, Rina Patriana (Humaniora, 2012)
Saman is a literature written by Ayu Utami. Showing a representation of a female counterpart ideology that differs from what has already been made in heterosexual and patriarchal society. The community considers sex is taboo to talk openly. In this novel it is represented openly. Women are no longer in a weak position, and have choices. In this paper, research methodology used is qualitative method.